Features of the Clinical Course, Complications and Lethality of Chronic Diffused Liver Diseases After Carrying Out Covid -19. (Eurasian Research Bulletin, 2023)
This article discusses the features of the clinical course of patients with chronic diffuse liver diseases (CDLD) against the background of COVID-19. The meta-analysis included 34 patients from the period 2022-2023, who were selected into two groups of cirrhosis and chronic hepatitis of the liver. Laboratory, clinical, instrumental data of patients were analyzed